2005
DOI: 10.1021/jp045410e
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Color Changes in Lamella Hybrids of Poly(diacetylenecarboxylates) Incorporated in Layered Double Hydroxide Nanosheets

Abstract: The present study is an investigation of a reversible thermal color change induced in lamella hybrids of poly(diacetylenecarboxylates) incorporated in layered double hydroxide (LDH) nanosheets. These poly-[m,n]/LDH hybrids prepared by the photo- or gamma-ray-induced polymerization of diacetylenecarboxylates, i.e., CH(3)(CH(2))(m)()(-)(1)CC-CC(CH(2))(n)()(-)(1)CO(2)(-) (mono-[m,n]), and intercalated in LDH lamella sheets, were observed to develop colors ranging from yellow to blue. The change in color was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 31 publications
(59 reference statements)
2
49
0
Order By: Relevance
“…Electron density distribution analysis in Figure 5 which represents the electron density distribution of the organoclay, estimated by the relation of ρ(x) against x (Equation (2)), supports the view that organoclay consists of alternatively stacked units of a bilayer sandwiched by clay platelets 20 . The X-ray diffraction patterns of the C 10 E 3 -organoclay show several diffraction peaks at the q located at 0.163, 0.34, 0.48 and 0.66 Å -1 .…”
Section: Resultssupporting
confidence: 61%
“…Electron density distribution analysis in Figure 5 which represents the electron density distribution of the organoclay, estimated by the relation of ρ(x) against x (Equation (2)), supports the view that organoclay consists of alternatively stacked units of a bilayer sandwiched by clay platelets 20 . The X-ray diffraction patterns of the C 10 E 3 -organoclay show several diffraction peaks at the q located at 0.163, 0.34, 0.48 and 0.66 Å -1 .…”
Section: Resultssupporting
confidence: 61%
“…[8] In general, the arrangement of interlayer guest anions can dramatically influence the physicochemical properties of LDH materials. [15][16][17][18] For example, in the case of poly(diacetylenecarboxylates) incorporated in LDHs, the possibility of having different arrangements of interlayer guests is responsible for the observed reversible thermal color changes. [18] In developing such functional materials it is important to be able to control the orientation of functional guest anions in the interlayer galleries in order to fully uti-lize their anisotropic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] For example, in the case of poly(diacetylenecarboxylates) incorporated in LDHs, the possibility of having different arrangements of interlayer guests is responsible for the observed reversible thermal color changes. [18] In developing such functional materials it is important to be able to control the orientation of functional guest anions in the interlayer galleries in order to fully uti-lize their anisotropic properties. An understanding of the factors controlling the interlayer arrangement is important if tailored applications in areas such as those mentioned above are to be found for LDHs containing [M(edta)] 2-complexes, but no such study has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…These materials were extensively investigated and evaluated as chemosensors and photonic materials. [14,15] Alternative deposition of oppositely charged linear polymers was also reported for the development of PDAbased chemosensors in layered PDA systems. [16] Zirconium oxide films were produced by sequential LBL adsorption of diluted zirconium alkoxide solutions onto a silicon wafer.…”
Section: Introductionmentioning
confidence: 97%